2020
DOI: 10.17569/tojqi.569211
|View full text |Cite
|
Sign up to set email alerts
|

Views on Interactive E-Book Use in Science Education of Teachers and Students Who Perform E-book Applications

Abstract: In parallel with the development in information and communication technologies, technology integration has been initiated in science education programs and lesson environments, and educational e-contents have been created by National Education and related institutions by making the books compatible with technology supported education. In parallel with this situation, the aim of the study was to obtain the interactive e-book views of the teachers and students performing the applications. This research, conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
0
14
0
1
Order By: Relevance
“…From this point of view, it is essential to support the use of digital education technologies such as interactive ebooks and e-content (Barate, Ludovico, & Mangione, 2014). However, it can be said that there is a lack of interactive science materials for technology integration in our country (Ormancı & Çepni, 2020).…”
Section: Tablo 5 Etkileşimli E-kitabın öğRenci Açısından Avantajlarımentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, it is essential to support the use of digital education technologies such as interactive ebooks and e-content (Barate, Ludovico, & Mangione, 2014). However, it can be said that there is a lack of interactive science materials for technology integration in our country (Ormancı & Çepni, 2020).…”
Section: Tablo 5 Etkileşimli E-kitabın öğRenci Açısından Avantajlarımentioning
confidence: 99%
“…ve bu alanda çalışmalar artırılmalıdır(Ormancı ve Çepni, 2020;Yıldırım, Baydaş ve Göktaş, 2017). Örneğin, Hakkari ve arkadaşlarının (2017) 9. sınıf öğrencileri ile yaptığı çalışmada etkileşimli e-kitap için 9.sınıf kimya dersi ile ilgili materyal geliştirip bu eğitimin öğrencilerin akademik başarılarına, kimya dersi ve teknolojiye yönelik tutumlarına, motivasyonlarına etkilerini nicel yöntem ile incelemişlerdir.…”
unclassified
“…Considering that the interactive e-books developed in this study have many positive effects on students, it is necessary to develop interactive e-books for other units in science education and happen in animation should be added to the page after animation. Also in terms of animation, it can be suggested that some animations in the literature can be attributed to three-dimensional animation, in particular (Ormancı & Çepni, 2020).…”
Section: Kamaludin Dwiyanto Wahyu Ari Nugroho Ridwan Suhud Rahmahwatimentioning
confidence: 99%
“…The advantages of E-Module includes; easily accessible (Abidin & Walida, 2019), can be designed with multiple media or multimedia (Suwatra et al, 2018), greater interactivity (Boticki et al, 2019), and being very affordable economically due to E-Module do not need to print. Other advantages of the E-module are Narration (text can be added with or highlighted) (Hsieh & Huang, 2020), Hot Spots (possibility of images, graphics, or text provided with a link with practice questions links), Audio (sound effects that can be included in the text), and Visual (images can be added with animation or video) (Bates et al, 2016;Ormancı & Çepni, 2020). In general, E-Module can be accessed by smartphones, laptops, or PCs (Handayani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%